Growth‐Related Formation Mechanism of I3‐Type Basal Stacking Fault in Epitaxially Grown Hexagonal Ge‐2H. Issue 16 (4th May 2022) - Vincent, Laetitia; Fadaly, Elham M. T.; Renard, Charles; Peeters, Wouter H. J.; Vettori, Marco; Panciera, Federico; Bouchier, Daniel; Bakkers, Erik P. A. M; Verheijen, Marcel A.
Abstract: The hexagonal‐2H crystal phase of Ge has recently emerged as a promising direct bandgap semiconductor in the mid‐infrared range providing new prospects of additional opto‐electronic functionalities of group‐IV semiconductors (Ge and SiGe). The controlled synthesis of such hexagonal‐2H Ge phase is a challenge that can be overcome by using wurtzite GaAs nanowires as a template. However, depending on growth conditions, unusual basal stacking faults (BSFs) of I3 ‐type are formed in the metastable 2H structure. The growth of such core/shell heterostructures is observed in situ and in real time by means of environmental transmission electron microscopy using chemical vapor deposition. The observations provide the first direct evidence of a step‐flow growth of Ge‐2H epilayers and reveal the growth‐related formation of I3 ‐BSFs during unstable growth. Their formation conditions are dynamically investigated. Through these in situ observations, a scenario can be proposed for the nucleation of I3 ‐type BSFs that is likely valid for any metastable hexagonal 2H or wurtzite structures grown on m‐plane substrates. Conditions are identified to avoid their formation for perfect crystalline synthesis of SiGe‐2H. Abstract : A controlled synthesis of hexagonal SiGe‐2H will provide the first Si‐based efficient light emitter. SiGe‐2H can be epitaxially grown on m‐plane surfaces of wurtzite GaAs. Avoiding the growth‐related I3 stacking faults is mandatory for optoelectronics properties. A step‐flow growth mode favors the reduction of defect density at low precursor flow and high temperature. A formation mechanism of I3 stacking faults is proposed.